2010
DOI: 10.1074/jbc.m109.068023
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Peroxidation Generates Body Odor Component trans-2-Nonenal Covalently Bound to Protein in Vivo

Abstract: trans-2-Nonenal is an unsaturated aldehyde with an unpleasant greasy and grassy odor endogenously generated during the peroxidation of polyunsaturated fatty acids. 2-Nonenal covalently modified human serum albumin through a reaction in which the aldehyde preferentially reacted with the lysine residues. Modified proteins were immunogenic, and a specific monoclonal antibody (mAb) 27Q4 that cross-reacted with the protein covalently modified with 2-nonenal was raised from mouse. To verify the presence of the prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
93
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(94 citation statements)
references
References 35 publications
1
93
0
Order By: Relevance
“…Zhu and Sayre (24) have previously identified a novel 4-ketoamide-type ONE-lysine adduct, N ⑀ -(4-oxononanoyl)lysine, that arises from a reversibly formed ONE-lysine Schiff base. We have also reported the formation of similar amide-type adducts upon reaction of the lysine derivative with n-alkanals in the presence of H 2 O 2 or alkyl hydroperoxides (25). Therefore, we hypothesized that HNE generated from HPNE might be involved in the formation of this product.…”
Section: Discussionmentioning
confidence: 99%
“…Zhu and Sayre (24) have previously identified a novel 4-ketoamide-type ONE-lysine adduct, N ⑀ -(4-oxononanoyl)lysine, that arises from a reversibly formed ONE-lysine Schiff base. We have also reported the formation of similar amide-type adducts upon reaction of the lysine derivative with n-alkanals in the presence of H 2 O 2 or alkyl hydroperoxides (25). Therefore, we hypothesized that HNE generated from HPNE might be involved in the formation of this product.…”
Section: Discussionmentioning
confidence: 99%
“…These longer alkenals are less reactive than acrolein or crotonaldehyde, possibly owing to their lower solubility in aqueous solvents that favour nucleophilic attack; this may explain why they have received less attention as molecules capable of modifying biomolecules. However, using an immunoreactivity assay and high performance liquid chromatography with on-line electrospray ionization tandem mass spectrometry it has been demonstrated that 2-nonenal can cause considerable protein modification, formed preferentially on lysine residues [41].…”
Section: Alkanalsmentioning
confidence: 99%
“…Less reactive than other 2-alkenals, such as acrolein and crotonaldehyde, so has received relatively little attention as an [41,136] x Lipid oxidation and fragmentation generates a wide variety of reactive alkanals, alkenals, bis-aldehydes and D-chlorofatty aldehydes.…”
Section: -Nonenal C9mentioning
confidence: 99%
“…4) prompted us to hypothesize that the ONL adduct could be recognized as a ligand by a membrane protein such as a scavenger receptor in the macrophages. Based on previous findings that the scavenger receptor LOX-1 might be involved in the processing of aldehyde-modified proteins (34,35) and that, among the aldehyde-treated proteins, the ONE-modified protein can be very efficiently incorporated into the LOX-1-overexpressing cells, 3 we sought to determine whether LOX-1 recognizes the ONL adduct. AcLDL was used as an alternative ligand to the OxLDL, which shows a comparable affinity to LOX-1 (36) to avoid ambiguous effects from variations in the extent of the oxidation of LDL (37,38).…”
Section: Lc-esi-ms/ms Analysis Of Onl-mentioning
confidence: 99%